2009
DOI: 10.1152/ajprenal.90589.2008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of D150E and G196D aquaporin-2 mutations responsible for nephrogenic diabetes insipidus: importance of a mild phenotype

Abstract: Aquaporin-2 (AQP2) is a water channel responsible for the final water reabsorption in renal collecting ducts. Alterations in AQP2 function induce nephrogenic diabetes insipidus (NDI), a condition characterized by severe polyuria and polydipsia. Three patients affected with severe NDI, who were compound heterozygous for the AQP2 mutations D150E and G196D, are presented here along with a mildly affected D150E homozygous patient from another family. Using Xenopus oocytes as an expression system, these two mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…In comparison to AQP2‐wt, when considering functionality (equivalent), plasma membrane targeting (equivalent) and protein abundance (20–40%), we find that K228E and V24A are the two most efficiently expressed AQP2 mutations evidenced so far in oocytes. Previous data, including ours (Guyon et al 2009 a ), globally reports overall efficiencies of about 1/10 or less (Marr et al 2002 a ; Robben et al 2006). With such functional characteristics in oocytes, V24A and even more K228E could basically be considered as functional variants of AQP2 with reduced expression levels, which may not satisfactory explain the NDI phenotype observed in compound mutation individuals.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In comparison to AQP2‐wt, when considering functionality (equivalent), plasma membrane targeting (equivalent) and protein abundance (20–40%), we find that K228E and V24A are the two most efficiently expressed AQP2 mutations evidenced so far in oocytes. Previous data, including ours (Guyon et al 2009 a ), globally reports overall efficiencies of about 1/10 or less (Marr et al 2002 a ; Robben et al 2006). With such functional characteristics in oocytes, V24A and even more K228E could basically be considered as functional variants of AQP2 with reduced expression levels, which may not satisfactory explain the NDI phenotype observed in compound mutation individuals.…”
Section: Discussionmentioning
confidence: 53%
“…4), which is in agreement with other reports using the same systems (Tamarappoo & Verkman, 1998; Yamauchi et al 1999; Marr et al 2001, 2002 b ). Even though oocytes and mammalian cells usually generate similar plasma membrane targeting results for AQP2 mutants (Guyon et al 2009 a ), the diverging targeting results found with K228E and V24A underline existing differences between both expression systems and stress the need to confirm key features such as targeting using a more appropriate cell model such as mIMCD‐3 cells. Thus, even though both K228E and V24A are functional proteins, the basic defect most probably resides in their profound inability to adequately reach the plasma membrane, worsened by a low protein synthesis level (20–40% in comparison to AQP2‐wt, in oocytes) and a possible lack of maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the cytoplasmic loop D, the D150E mutant has been identified in patients suffering from recessive NDI (34,35). Our X-ray structure reveals that Asp150 mediates an interaction between loop D and the proximal end of the C-terminal tail, with Asp150 connecting to Pro225 via hydrogen bonds mediated by Arg152 (Fig.…”
Section: Camentioning
confidence: 76%
“…Since both mutations are well described in literature [45], correlations of protein energy/stability and experimental observations can be developed.…”
Section: Methodsmentioning
confidence: 99%